Evaluation of mycorrhizal application in overcoming soil water limitations in cocoa seedlings - Sakiroh; Sasmita, Kurnia Dewi; Sobari, Iing; Wardiana, Edi; Hafif, Khaeratib, Bariot; Putra, Sunjaya; Supriadi, Handi; Herman, Maman; Saefudin; Ferry, Yulius; Rokhmah, Dewi Nur; Pranowo, Dibyo; et al. (Agriculture and Natural Resources, 2026)
Importance of the work: Mycorrhiza could play a major role in overcoming soil water limitations that restrict crop growth. Objectives: To evaluate the impact of mycorrhizal application on enhancing cocoa seedling resilience to water limitations in the soil. Materials and Methods: The experiment was conducted using a split-plot design based on a randomized block design. The main plot had two soil moisture levels: 100% and 50% f ield capacity. The sub-plots were applications of different mycorrhizae: M0, CM, CGK1, CGK2, CGK3, CGK4, CGK5, CS1, CS2, ACS1, ACS2, ACS3 and RCS. Results: The 12 mycorrhizae evaluated had different responses to soil moisture levels. The soil moisture level at 50% field capacity in the control treatment significantly reduced the nitrogen uptake, seedling height, shoot fresh weight and shoot dry weight of cocoa seedlings; however, it did not cause drought stress. These four variables served as indicators for evaluating mycorrhizal applications in managing soil moisture levels at 50% field capacity. Consistently, the mycorrhizae CGK3, ACS3 and RCS exhibited similar performance at both 50% and 100% field capacity across these four indicator variables. Main finding: The identification of three mycorrhizae, CGK3, ACS3 and RCS, could enhance the diversity of mycorrhizae that help cocoa seedlings overcome soil water limitations.